The Influence Of Work Enthusiasm And Work Discipline On The Work Productivity Of Employees Of The Fisheries Service Of The Four Lawang District - Wati, Putri Setia; Hardiyansyah; Aprini , Nisma (Journal of Management, Economic, and Accounting, 2024)
abstrak